Enhancing Robustness of Sortase A by Loop Engineering and Backbone Cyclization. Issue 60 (18th August 2020) - Zou, Zhi; Mate, Diana M.; Nöth, Maximilian; Jakob, Felix; Schwaneberg, Ulrich
Abstract: Staphylococcus aureus sortase A (SaSrtA) is widely used for site‐specific protein modifications, but it lacks the robustness for performing bioconjugation reactions at elevated temperatures or in presence of denaturing agents. Loop engineering and subsequent head‐to‐tail backbone cyclization of SaSrtA yielded the cyclized variant CyM6 that has a 7.5 °C increased melting temperature and up to 4.6‐fold increased resistance towards denaturants when compared to the parent rM4. CyM6 gained up to 2.6‐fold (vs. parent rM4) yield of conjugate in ligation of peptide and primary amine under denaturing conditions. Abstract : Protein engineering : Semi‐rational loop engineering and subsequent head‐to‐tail backbone cyclization of Staphylococcus aureus sortase A (SaSrtA) yielded a cyclized variant CyM6 with enhanced activity and robustness towards thermal and chemical denaturation (see figure).